Pengaruh Kepemilikan Keluarga, Kondisi Keuangan Dan Ukuran Kap Terhadap Audit Report Lag - Raihana, Ashfi; Achmad, Komarudin (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to determine the effect of family ownership, financial condition, and Public Accounting Firm size, on audit report lag of 492 manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2021. The data includes the companies’ financial statements collected through documentation from the IDX official website. The samples are selected through purposive sampling method, and are analyzed by multiple regression utilizing SPSS 26 software. The results revealed that family ownership had a negative effect on audit report lag. Whilst, financial condition had a positive effect on audit report lag and Public Accounting Firm size had a negative effect on audit report lag.